Cosec-sin=m3 and sec-cos=n3 then prove that m4n2+m2n4=1
Answers
Answered by
8
As we know that
![cosec \: x = \frac{1}{sin \: x} \\ \\ sec \: x = \frac{1}{cos \: x} \\ \\ cosec \: x = \frac{1}{sin \: x} \\ \\ sec \: x = \frac{1}{cos \: x} \\ \\](https://tex.z-dn.net/?f=cosec+%5C%3A+x+%3D++%5Cfrac%7B1%7D%7Bsin+%5C%3A+x%7D++%5C%5C++%5C%5C+sec+%5C%3A+x+%3D++%5Cfrac%7B1%7D%7Bcos+%5C%3A+x%7D++%5C%5C++%5C%5C+)
Given
![cosec \: x - sin \: x = {m}^{3} \\ \\ \frac{1}{sin \: x} - sin \: x = {m}^{3} \\ \\ \frac{1 - {sin}^{2}x }{sin \: x} = {m}^{3} \\ \\ \frac{ {cos}^{2}x }{sin \: x} = {m}^{3} ...eq1\\ \\ cosec \: x - sin \: x = {m}^{3} \\ \\ \frac{1}{sin \: x} - sin \: x = {m}^{3} \\ \\ \frac{1 - {sin}^{2}x }{sin \: x} = {m}^{3} \\ \\ \frac{ {cos}^{2}x }{sin \: x} = {m}^{3} ...eq1\\ \\](https://tex.z-dn.net/?f=cosec+%5C%3A+x+-+sin+%5C%3A+x+%3D++%7Bm%7D%5E%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Bsin+%5C%3A+x%7D++-+sin+%5C%3A+x+%3D++%7Bm%7D%5E%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B1+-++%7Bsin%7D%5E%7B2%7Dx+%7D%7Bsin+%5C%3A+x%7D++%3D++%7Bm%7D%5E%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B+%7Bcos%7D%5E%7B2%7Dx+%7D%7Bsin+%5C%3A+x%7D++%3D++%7Bm%7D%5E%7B3%7D++...eq1%5C%5C++%5C%5C+)
By the same way
![sec \: x - cos \: x = {n}^{3} \\ \\ \frac{1}{cos \: x} - cos \: x = {n}^{3} \\ \\ \frac{1 - {cos}^{2}x }{cos \: x} = {n}^{3} \\ \\ \frac{ {sin}^{2}x }{cos \: x} = {n}^{3} ...eq2\\ \\ sec \: x - cos \: x = {n}^{3} \\ \\ \frac{1}{cos \: x} - cos \: x = {n}^{3} \\ \\ \frac{1 - {cos}^{2}x }{cos \: x} = {n}^{3} \\ \\ \frac{ {sin}^{2}x }{cos \: x} = {n}^{3} ...eq2\\ \\](https://tex.z-dn.net/?f=sec+%5C%3A+x+-+cos+%5C%3A+x+%3D++%7Bn%7D%5E%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Bcos+%5C%3A+x%7D++-+cos+%5C%3A+x+%3D++%7Bn%7D%5E%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B1+-++%7Bcos%7D%5E%7B2%7Dx+%7D%7Bcos+%5C%3A+x%7D++%3D++%7Bn%7D%5E%7B3%7D++%5C%5C++%5C%5C++%5Cfrac%7B+%7Bsin%7D%5E%7B2%7Dx+%7D%7Bcos+%5C%3A+x%7D++%3D++%7Bn%7D%5E%7B3%7D++...eq2%5C%5C++%5C%5C++)
Squaring both side eq1
![\frac{ {sin}^{4}x }{ {cos}^{2} \: x} = {n}^{6} \\ \\ put \: value \: of \: {cos}^{2} x \: from \: second \: equation \\ \\ \frac{ {sin}^{4}x }{ {m}^{3} sin\: x } = {n}^{6} \\ \\ {sin}^{3} x = {m}^{3} {n}^{6} \\ \\ {sin}^{3}\: x = ( {m {n}^{2} })^{3} \\ \\ compare \: base \: sin \: x = m {n}^{2} \\ \\ \frac{ {sin}^{4}x }{ {cos}^{2} \: x} = {n}^{6} \\ \\ put \: value \: of \: {cos}^{2} x \: from \: second \: equation \\ \\ \frac{ {sin}^{4}x }{ {m}^{3} sin\: x } = {n}^{6} \\ \\ {sin}^{3} x = {m}^{3} {n}^{6} \\ \\ {sin}^{3}\: x = ( {m {n}^{2} })^{3} \\ \\ compare \: base \: sin \: x = m {n}^{2} \\ \\](https://tex.z-dn.net/?f=%5Cfrac%7B+%7Bsin%7D%5E%7B4%7Dx+%7D%7B+%7Bcos%7D%5E%7B2%7D+%5C%3A+x%7D++%3D++%7Bn%7D%5E%7B6%7D++%5C%5C++%5C%5C+put+%5C%3A+value+%5C%3A+of+%5C%3A++%7Bcos%7D%5E%7B2%7D+x+%5C%3A+from+%5C%3A+second+%5C%3A+equation+%5C%5C++%5C%5C+%5Cfrac%7B+%7Bsin%7D%5E%7B4%7Dx+%7D%7B+%7Bm%7D%5E%7B3%7D+sin%5C%3A+x+%7D++%3D++%7Bn%7D%5E%7B6%7D+%5C%5C++%5C%5C++%7Bsin%7D%5E%7B3%7D+x+%3D++%7Bm%7D%5E%7B3%7D++%7Bn%7D%5E%7B6%7D++%5C%5C++%5C%5C++%7Bsin%7D%5E%7B3%7D%5C%3A+x+%3D+%28+%7Bm+%7Bn%7D%5E%7B2%7D+%7D%29%5E%7B3%7D++%5C%5C++%5C%5C+compare+%5C%3A+base+%5C%3A+sin+%5C%3A+x+%3D+m+%7Bn%7D%5E%7B2%7D++%5C%5C++%5C%5C+)
Thus put the value of sin x in any equation and find cos x,
![cos \: x = n {m}^{2} \\ \\ cos \: x = n {m}^{2} \\ \\](https://tex.z-dn.net/?f=cos+%5C%3A+x+%3D+n+%7Bm%7D%5E%7B2%7D++%5C%5C++%5C%5C+)
Now we know that
![{sin}^{2} x + {cos}^{2} x = 1 \\ \\ ({m {n}^{2} })^{2}+ {(n {m}^{2})}^{2} = 1 \\ \\ {m}^{2} {n}^{4} + {n}^{2} {m}^{4} = 1 \\ \\ {sin}^{2} x + {cos}^{2} x = 1 \\ \\ ({m {n}^{2} })^{2}+ {(n {m}^{2})}^{2} = 1 \\ \\ {m}^{2} {n}^{4} + {n}^{2} {m}^{4} = 1 \\ \\](https://tex.z-dn.net/?f=+%7Bsin%7D%5E%7B2%7D+x+%2B++%7Bcos%7D%5E%7B2%7D+x+%3D+1+%5C%5C++%5C%5C++%28%7Bm+%7Bn%7D%5E%7B2%7D+%7D%29%5E%7B2%7D%2B++%7B%28n+%7Bm%7D%5E%7B2%7D%29%7D%5E%7B2%7D+%3D+1+%5C%5C++%5C%5C++%7Bm%7D%5E%7B2%7D++%7Bn%7D%5E%7B4%7D++%2B++%7Bn%7D%5E%7B2%7D++%7Bm%7D%5E%7B4%7D++%3D+1+%5C%5C++%5C%5C+)
Hence proved
Given
By the same way
Squaring both side eq1
Thus put the value of sin x in any equation and find cos x,
Now we know that
Hence proved
Similar questions